Membangun Manajemen Pendidikan Islam yang Adaptif: Integrasi Nilai Moral dalam Pembentukan Karakter Siswa (Indo-MathEdu Intellectuals Journal, 2025)
This study analyzes the gap between academic achievement and moral character development in Islamic education, focusing on the integration of life values as the foundation for developing theories and practices in Islamic education management. The research employed a library research method, utilizing data sources such as journal articles, books, and relevant research reports. Data collection techniques involved selecting literature based on topic relevance, source credibility, and validity. Data analysis was conducted using analytical and synthetic methods to identify patterns, concepts, and research gaps. The findings reveal significant challenges in Islamic education, including insufficient teacher training, limited value-based curricula, and the impact of globalization and social media, which have contributed to a decline in students' moral values. Although value-based approaches have proven conceptually effective in building students' character, practical implementation continues to face systemic barriers. This study emphasizes the importance of curriculum reform and the development of value-based educational management models that are adaptive to modern needs while maintaining Islamic identity. It provides a robust conceptual foundation for further comprehensive research to create relevant, holistic, and morally-oriented Islamic education systems